Cracking the New Job Market : the 7 Rules for Getting Hired in Any Economy. - Holland, R. William (AMACOM, 2011)
The rules for finding professional work once seemed clear and unwavering: capture career highlights in a resume, practice answers to standard interview questions, and do lots of face-to-face networking. "Cracking the New Job Market" shows how these rules have changed and delivers new job-hunting strategies that actually work. The key, rather than to emphasize past accomplishments, is to sell your self on the value you can create for an employer. This new approach to getting hired requires new skills. Author R. Willam Holland, a human resources insider, shows job seekers how to: gathe.